Práticas pedagógicas em ambiente virtual de aprendizagem : possibilidades de inovação - Boeira, Jocelaine Minella (My University, 2014)
This study had as objective to examine the records of the teachers of Primary and final year of High School, a private school in the city of Bento Gonçalves, Rio Grande do Sul, a training course to use a virtual learning environment (VLE) and relate them to possible changes in teaching practices. The study proposes to conduct a qualitative research based on data obtained through the records of studentteachers in the spaces of VLE. Were invited to be the subjects in the study were eight teachers of Basic Education, the final years of Primary and Secondary Education. The corpus consisted of records present in the space communication environment (forum, lessons, electronic mail). The development of the training course that provided the backdrop for the constitution of the corpus, was planned from the viewpoint of learning from Vigotski theory as well as encourage participants to reflect on the pedagogical seeking innovative pedagogical practice from the perspective of Moran (2007, 2008). The corpus analysis was made in light of Moraes and Galiazzi (2007) with discursive textual analysis, which consists of three cycles called by the authors as deconstruction and unitarization; categorization process and production of an interpretive-descriptive text (metatext). From the analysis it was possible to identify possible changes in pedagogical future of student-teachers, characterized by pedagogical strategies and interventions that lead to knowledge construction through interaction and collaboration among peers.
Esta investigação teve como objetivo principal examinar os registros dos professores do Ensino Fundamental, anos finais, e do Ensino Médio, de uma escola particular, do município de Bento Gonçalves, Rio Grande do Sul, num curso de capacitação para utilizar um Ambiente Virtual de Aprendizagem (AVA) e relacionálas com possíveis mudanças nas práticas pedagógicas. O trabalho se propôs a realizar uma pesquisa de natureza qualitativa baseada nos dados obtidos através dos registros dos professores-alunos nos espaços do AVA. Foram convidados para serem os sujeitos na pesquisa oito professores da Educação Básica, anos finais do Ensino Fundamental e Ensino Médio. O corpus da pesquisa constituiu-se dos registros presentes nos espaços de comunicação do ambiente (fórum, lições, correio eletrônico). O desenvolvimento do curso de capacitação que serviu de cenário para constituição do corpus, foi planejado sob o ponto de vista da aprendizagem a partir da teoria vigotskiana, assim como estimular os participantes a refletirem sobre o fazer pedagógico buscando a prática pedagógica inovadora sob a visão de Moran (2007; 2008). A análise do corpus foi feita à luz de Moraes e Galiazzi (2007) com análise textual discursiva, a qual é constituída por três ciclos denominado pelos autores como: desconstrução e unitarização; processo de categorização e produção de um texto descritivo-interpretativo (metatexto). A partir da análise foi possível identificar possíveis mudanças no fazer pedagógico futuro dos professores-alunos, caracterizadas por estratégias e intervenções pedagógicas que remetem a construção de conhecimentos através da interação e colaboração entre os pares.
Keywords: Educação; Práticas pedagógicas; Sociointeração; Ambiente virtual de aprendizagem; Capacitação; Prática de ensino; Aprendizagem; Ensino auxiliado por computador; Ambiente virtual; Pedagogical practices; Social interaction; Virtual learning environment; Training; Student teaching; Learning; Computer-assisted instruction; Virtual environment